THE INFLUENCE OF COMPENSATION ON EMPLOYEE LOYALITY AT PT SURYA PILAR PERKASA PEKANBARU - Saiful Anuar (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
This research was conducted at PT. SURYA PILAR PERKASA. One way used to increase employee loyalty for companies is compensation. Compensation is a form of reward received by employees in lieu of services they have provided to the company. The purpose of this study is to determine the effect of compensation on employee loyalty PT. Surya Pillars of Might. The population in this study were 85 employees. The sample taken is the whole of the population of 85 employees. For the regression of linear analysis, the regression equation is generated as follows: Y = 6.464 + 1.421.X and the constant value of 6.464 states that if the value of X = 0 or Compensation variable does not exist, then the value of Employee Loyalty variable is 6.464. The regression coefficient of the Compensation variable is 1.421, meaning that every addition of 1 (one) variable point of Compensation, then it will increase employee loyalty equal to 1.421 times. The interpretation of the equation above is that the variable regression coefficient of Compensation (X) has a positive sign (1.421), which implies that Compensation is in line with Employee Loyalty variable, in other words that the Compensation variable has a positive effect on Employee Loyalty. Based on the value of t, obtained t-count of 2.952 at the sig level of 0.000. The calculation results show that Compensation has t arithmetic larger than t table that is 2.952> 1,988 which means Ho is rejected so Ha accepted. It can be concluded that the Compensation variable has a significant influence on employee loyalty in PT.Surya Pilar Perkasa Pekanbaru. Furthermore, R2 value of 0.669. Because this coefficient determination test obtained from simple linear regression calculation, the coefficient of determination of 0.669 or R2 x 100% by 67%. The meaning of the value has the implication that the compensation variable affects Loyalty by 67%, and the rest is influenced by other variables. Keywords: Compensation, Loyalty